Toward a Software Architecture for Quantum Computing Design Tools - Svore, Krysta M.; Cross, Andrew; Aho, Alfred V.; Chuang, Isaac; Markov, Igor; Svore, Krysta M. (Proceedings of Quantum Programming Languages (QPL), 2004)
Compilers and computer-aided design tools will be essential for quantum computing. We present a computer-aided design flow that transforms a high-level language program representing a quantum computing algorithm into a technology-specific implementation. We trace the significant steps in this flow and illustrate the transformations to the representation of the quantum program. The focus of this paper is on the languages and transformations needed to represent and optimize a quantum algorithm along the design flow. Our software architecture provides significant benefits to algorithm designers, tool builders, and experimentalists. Of particular interest are the trade-offs in performance and accuracy that can be obtained by weighing different optimization and error-correction procedures at given levels in the design hierarchy.